Detection of Candida albicans from Positive Blood Culture Bottles - Saad, Uzma; iSddiqui, Sualleha; Jamil, Naz; Jamil, Sana; Hafiz, Saleem (International Journal of Pathology, 2018)
Objective: To determine the efficacy of direct germ tube method in early detections of candida albicans.Introduction: Blood stream infections (BSIs) caused by Candida species are on the increase and associatedwith high mortality rates, which are due in part to delay in the administration of appropriate antifungaltherapy. Earlier identification of yeast isolates from blood cultures may improve clinical outcomes.Identification of Candida as albicans or non-albicans species depends on the presence or absenceof germ tubes. Rapid differentiation of C.albicans from non- albicans is made on its ability to producegerm tubes after incubation in human serum.Materials and Methods: Germ tube test (GTT) is performed on colonies grown on agar plate after 24–48 h of incubation. In our study, we performed GTT directly on the aliquot taken from positive bloodculture bottles and yeast cells seen in Gram stain. The results were compared with GTT using the conventionalmethod.Results: Out of 100 positive blood cultures with yeast like cells on gram stain only eight were positivefor Candida albicans by both the methods. There was 100 % concordance between the direct GTT and theGTT performed from the subcultured organisms grown on solid media.Conclusion: Early detection of species of Candida using the Direct Germ Tube method is of utmostimportance for early initiation of appropriate anti-fungal therapy in order to reduce morbidity andmortality of patients with candidemia.